2020
DOI: 10.4236/ajps.2020.112012
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Fusion Lytic Peptides Promotes Fungal Disease Resistance in Transgenic Plants

Abstract: Many organisms produce small proteins which exhibit antimicrobial activities. In recent decades, the biological role of antimicrobial peptides (AMP) has been recognized as the main factor in the defense mechanisms against a broad range of pathogenic microbes. The increased worldwide incidence of microbial resistance to antibiotics makes AMPs promising alternative for the control of microbial disease. Exploring the potential of AMPs in transgenic crops could lead to the development of new and improved cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…citri was enhanced in comparison with nontransgenic lines (He et al, 2011). Biliarski et al (2020) expressed two fusion lytic peptides, ORF13 and RSL1, in Nicotiana benthamiana tobacco plants, and then tested their resistance activity against three fungal pathogens, Sclerotinia sclerotiorum, Rhizoctonia solani, and Pythium species. The symptom area of each leaf was measured, and found that the transgenic plant lines ORF13 and RSL1 had resistance against Sclerotinia sclerotiorum and Rhizoctonia solani.…”
Section: Applications In Agriculturementioning
confidence: 99%
“…citri was enhanced in comparison with nontransgenic lines (He et al, 2011). Biliarski et al (2020) expressed two fusion lytic peptides, ORF13 and RSL1, in Nicotiana benthamiana tobacco plants, and then tested their resistance activity against three fungal pathogens, Sclerotinia sclerotiorum, Rhizoctonia solani, and Pythium species. The symptom area of each leaf was measured, and found that the transgenic plant lines ORF13 and RSL1 had resistance against Sclerotinia sclerotiorum and Rhizoctonia solani.…”
Section: Applications In Agriculturementioning
confidence: 99%